A method of screen printing a patterned perovskite film
Patent Information
- Application Number
- CN202511915105.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-18
- Publication Date
- 2026-09-11
AI Technical Summary
[0005]针对现有技术存在的“大面积制备与高精度图案化难以兼顾、加工过程易引入污染”的不足之处,本发明的目的旨在提供一种丝网印刷制备图案化钙钛矿薄膜的方法,该方法采用丝网印刷的方式,将浆料印刷到浸润性模板上,实现钙钛矿薄膜的图案化
Smart Images

Figure CN122742610A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of perovskite thin film preparation technology, specifically relating to a method for preparing patterned perovskite thin films by screen printing. Background Technology
[0002] Perovskite materials have shown great application potential in the fields of photovoltaics and optoelectronic devices due to their advantages such as high photoelectric conversion efficiency, low cost, and solution-processability. However, the synergistic realization of large-area molding, high-precision patterning, and green and pollution-free processing has become the core issue restricting the industrialization of these materials.
[0003] Existing perovskite thin film preparation technologies struggle to meet the aforementioned core requirements: spin coating, while capable of producing high-quality films, is only suitable for small-area substrates at the square centimeter level, resulting in low material utilization and the inability to directly achieve patterning; blade coating can expand the preparation area, but requires secondary processes such as etching and masking for patterning, increasing process complexity and easily introducing pollutants such as chemical etchants, damaging perovskite crystallinity and causing environmental burden; vapor deposition, while capable of patterning, suffers from high costs and low efficiency due to its vacuum processing mode, making it unsuitable for large-area preparation at the square meter level, and the organometallic source is prone to volatilization, generating toxic gases and posing a pollution risk; inkjet printing, while capable of patterning, suffers from poor slurry compatibility, is prone to pinhole defects, has low printing efficiency, and the organic solvents used are prone to volatilization, polluting the air and failing to meet green manufacturing requirements.
[0004] In summary, existing technologies generally suffer from drawbacks such as difficulty in simultaneously achieving large-area fabrication and high-precision patterning, and the potential for pollution during processing, failing to meet the demands for large-scale, green production of perovskite devices. Therefore, developing a fabrication technology that enables large-area, high-precision patterning of perovskite slurry, with zero pollutant emissions and an environmentally friendly processing method, has become a critical issue urgently needing to be addressed in this field. Summary of the Invention
[0005] In view of the shortcomings of existing technologies, such as "difficulty in achieving both large-area preparation and high-precision patterning, and easy introduction of contamination during processing", the present invention aims to provide a method for preparing patterned perovskite thin films by screen printing. This method uses screen printing to print paste onto a wettable template to achieve patterning of the perovskite thin film.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing patterned perovskite thin films by screen printing, comprising the following steps: S1. Substrate cleaning: Cut the substrate to the required size, clean it with a lint-free cloth and ethanol, place it on a PTFE cleaning rack, put it in an ultrasonic cleaner, add water and ethanol alternately in sequence, and ultrasonically clean it. After ultrasonic cleaning, remove the substrate and dry it with nitrogen. S2, hydrophilic treatment: Place the substrate cleaned by S1 into a plasma cleaner or a UV ozone cleaner for hydrophilic treatment. S3, Perovskite slurry preparation: After dry grinding of perovskite single crystals, a binary mixed solvent is added, and the mixture is wet ground until homogeneous to obtain a perovskite slurry. The raw material ratio is perovskite single crystal : binary mixed solvent = (3~5) g : (100~200) μL. The binary mixed solvent is prepared by mixing ethylene glycol and hydrohalic acid solution at a mass ratio of a : (100-a) and stirring until homogeneous. The value of a ranges from 24 to 48. The halogen in the hydrohalic acid is the same as that in the perovskite single crystal, and the concentration of the hydrohalic acid solution is 45~58 wt%. S4. Screen printing for preparing patterned perovskite wet films: A patterned stencil is horizontally fixed, and the substrate obtained in S2 is placed below the area to be printed on the stencil. The perovskite slurry obtained in S3 is evenly applied to the area to be printed on the stencil. The stencil is then pressed down with a squeegee until it contacts the substrate and passes through the area to be printed, thus obtaining a patterned perovskite wet film on the substrate. The pattern on the stencil corresponds to a preset pattern on the perovskite film: the preset pattern portion of the perovskite film is solid, and the corresponding pattern portion on the stencil is hollow; the preset pattern portion of the perovskite film is hollow, and the corresponding pattern portion on the stencil is solid; the stencil area corresponding to the area of the perovskite film without a preset pattern is solid. S5. Annealing treatment: The patterned perovskite wet film printed by S4 is annealed together with the substrate to obtain a patterned perovskite thin film.
[0007] Preferably, in S1, the substrate is quartz, glass, silicon wafer or other flexible substrate.
[0008] Preferably, in S2, the contact angle of the substrate after hydrophilic treatment is 0~50°.
[0009] Preferably, in S3, the perovskite single crystal includes, but is not limited to, MAPbI3, PEA2PbI4, and BA2MA3Pb4I. 13 Or Cs2AgBiBr6.
[0010] Ideally, in S4, the mesh count of the stencil is 50 to 200 mesh.
[0011] Ideally, in S5, the annealing conditions are 60~80℃ for 30~60min.
[0012] The key points of this invention are: hydrophilic substrate treatment + perovskite slurry preparation + perovskite film screen printing.
[0013] The principle of this invention is as follows: a perovskite single crystal is ground and then ground again with an aqueous binary mixed solvent in a preset ratio to prepare a perovskite slurry; the substrate is treated with a plasma cleaner or an ultraviolet ozone cleaner, and hydrophilic groups are attached to the surface of the substrate after treatment to improve hydrophilicity, so that the perovskite slurry can better contact the substrate according to the shape of the mesh to form a perovskite film with a preset pattern.
[0014] In this invention, perovskite single crystals can be obtained either by purchasing them from the market or by preparing them using existing techniques. For example, MAPbI3 can be obtained by referring to the literature: D. Raffaele Ceratti, R.enne, et al. Adv. Mater. 2022,34, 21102); PEA2PbI4 can be obtained by referring to the literature: Z. Rui, Y. Chen-Quan, et al. ACS Energy Lett. 2023, 8, 2620−2629; BA2MA3Pb4I 13 (See references: C. Stoumpos, C. Duyen H, et al. Chem. Mater. 2016, 28, 2852-2867); Cs2AgBiBr6 can be found in reference: L. Hongwei, D. Hardy, et al. Adv. Funct. Mater. 2021, 31, 2105.)
[0015] Beneficial effects: The screen printing method of this invention can be used for large-area patterning; compared with other organic solvents, the preparation of the paste uses a water-based solvent, which is green and pollution-free. This method has important practical significance for promoting the large-scale, low-cost manufacturing of perovskite optoelectronic devices from the laboratory. Attached Figure Description
[0016] Figure 1 A schematic diagram of the process for preparing patterned perovskite thin films by screen printing.
[0017] Figure 2 This is an image showing the pattern effect on the screen.
[0018] Figure 3 Optical microscope images of the patterned perovskite slurry films prepared in Examples 1 and 2: Figure 3 a is prepared according to Example 1. Figure 3 b is prepared as in Example 2.
[0019] Figure 4Optical microscope images of the patterned perovskite thin films prepared in Examples 3 to 6: Figure 4 a is prepared according to Example 3. Figure 4 b is prepared according to Example 4. Figure 4 c is prepared according to Example 5. Figure 4 d is prepared according to Example 6.
[0020] Figure 5 Optical microscope images of the perovskite thin films prepared in Comparative Examples 1 to 4: Figure 5 a was prepared as control example 1; Figure 5 b was prepared as control example 2; Figure 5 c was prepared as control example 3; Figure 5 d was prepared as control example 3.
[0021] Figure 6 The profilometer analysis results of the perovskite thin film prepared in Example 1 are shown in the following graphs: the upper graph shows the profilometer scanning area, and the lower graph shows the scanning results.
[0022] Figure 7 The profilometer analysis results of the perovskite thin film prepared in Comparative Example 2 are shown in the following graphs: the upper graph shows the profilometer scanning area, and the lower graph shows the scanning results.
[0023] Figure 8 The profilometer analysis results of the perovskite thin film prepared in Comparative Example 3 are shown in the following graphs: the upper graph shows the profilometer scanning area, and the lower graph shows the scanning results.
[0024] Figure 9 The profilometer analysis results of the perovskite thin film prepared in Comparative Example 4 are shown in the following graphs: the upper graph shows the profilometer scanning area, and the lower graph shows the scanning results. Detailed Implementation
[0025] To enable those skilled in the art to better understand the technical solutions of the present invention, the present invention will be further described below in conjunction with specific embodiments. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the described embodiments, all other embodiments obtained by those skilled in the art without creative effort are within the protection scope of the present invention.
[0026] Example 1
[0027] A method for preparing patterned perovskite thin films by screen printing, the process is as follows: Figure 1 As shown, the steps are as follows: S1. Substrate cleaning: Cut the substrate (silicon wafer) into the required size, clean it with a lint-free cloth and anhydrous ethanol, place it on a polytetrafluoroethylene cleaning rack, and put it in an ultrasonic cleaner. Add deionized water and anhydrous ethanol alternately and ultrasonically clean it. After ultrasonic cleaning, remove the substrate and dry it with nitrogen. S2, hydrophilic treatment: The substrate cleaned by S1 was placed in a plasma cleaner for hydrophilic treatment. After hydrophilic treatment, the contact angle of the substrate was 20°. S3, Perovskite slurry preparation: After dry grinding 3.6g of MAPbI3 single crystal, 100μL of binary mixed solvent was added, and wet grinding was carried out until uniform to obtain perovskite slurry; wherein, the binary mixed solvent was prepared by mixing ethylene glycol and HI aqueous solution (concentration 55wt%) in a mass ratio of 36:64 and stirring until uniform. S4. Screen printing for preparing patterned perovskite wet films: Fix the 100-mesh screen horizontally; the pattern on the screen is as follows. Figure 2 As shown in a, the substrate obtained in S2 is placed below the area to be printed on the stencil; the perovskite slurry obtained in S3 is evenly applied to the area to be printed on the stencil, and the squeegee is used to press the stencil down until it contacts the substrate and passes through the area to be printed, so that a patterned perovskite wet film is obtained on the substrate. S5. Annealing treatment: The patterned perovskite wet film printed by S4, together with the substrate, was annealed at 70°C for 40 minutes to obtain a patterned perovskite thin film.
[0028] Example 2
[0029] The difference from Example 1 is that in S4, the pattern on the screen is changed to... Figure 2 As shown in b; everything else is the same as in Example 1.
[0030] Example 3
[0031] The difference from Example 1 is that in S4, the pattern on the screen is changed to... Figure 2 As shown in c; everything else is the same as in Example 1.
[0032] Example 4
[0033] The difference from Example 1 is that in S3, "PEA2PbI4 single crystal" is used instead of "MAPbI3 single crystal"; in S4, the pattern on the stencil is changed to... Figure 2 As shown in c; everything else is the same as in Example 1.
[0034] Example 5
[0035] The difference from Example 1 is that in S3, "BA2MA3Pb4I" is used. 13 "Single crystal" replaces "MAPbI3 single crystal"; in S4, the pattern on the stencil is changed to... Figure 2 As shown in c; everything else is the same as in Example 1.
[0036] Example 6
[0037] The difference from Example 1 is that in step S3, "Cs2AgBiBr6 single crystal" is used instead of "MAPbI3 single crystal", and "HBr aqueous solution (concentration 55wt%)" is used instead of "HI aqueous solution"; in S4, the pattern on the screen is changed to Figure 2 As shown in c; everything else is the same as in Example 1.
[0038] Comparative Examples 1 to 4 To investigate the effect of the composition of a binary mixed solvent on perovskite thin films using a profilometer, and considering that screen printing cannot produce small patterns that are inconvenient for testing, a titration method was used instead. The specific experimental procedure is as follows: S1. Substrate cleaning: Cut the substrate to the required size, clean it with a lint-free cloth and anhydrous ethanol, place it on a PTFE cleaning rack, and put it in an ultrasonic cleaner. Add deionized water and anhydrous ethanol alternately in sequence and ultrasonically clean each time. After ultrasonic cleaning, remove the substrate and dry it with nitrogen. S2, hydrophilic treatment: The substrate cleaned by S1 was placed in a plasma cleaner for hydrophilic treatment. After hydrophilic treatment, the contact angle of the substrate was 20°. S3, Perovskite slurry preparation: After dry grinding 3.6g of MAPbI3 single crystal, 100μL of binary mixed solvent was added, and wet grinding was carried out until uniform to obtain perovskite slurry; wherein, the binary mixed solvent was prepared by mixing ethylene glycol and HI aqueous solution (concentration 55wt%) according to the mass ratio shown in Table 1 and stirring until uniform. ; S4. Titration for film formation: 0.1 μL of the perovskite slurry obtained from S3 was dropped onto the substrate using a pipette and allowed to flow naturally to form a film, thus obtaining a wet perovskite film. S5. Annealing treatment: The perovskite wet film obtained in S4, together with the substrate, was annealed at 70°C for 40 min to obtain a perovskite thin film.
[0039] Characterization results Optical photographs of the patterned perovskite thin films prepared in Examples 1 and 2 (taken using a Century Kexin optical microscope, the same below) are shown below. Figure 3 As shown: Figure 3 a is prepared according to Example 1. Figure 3 b is prepared as in Example 2.
[0040] Optical microscope images of the patterned perovskite thin films prepared in Examples 3-6 are shown below. Figure 4 As shown: Figure 4 a is prepared according to Example 3. Figure 4 b is prepared according to Example 4. Figure 4 c is prepared according to Example 5. Figure 4 d is prepared according to Example 6.
[0041] Optical microscope images of the perovskite thin films prepared in Comparative Examples 1 to 4 are shown below. Figure 5 As shown: Figure 5 a was prepared as control example 1; Figure 5 b was prepared as control example 2; Figure 5 c was prepared as control example 3; Figure 5 d was prepared as control example 4. Figure 6 The profilometer analysis results of the perovskite thin film prepared in Example 1 are shown in the following graphs: the upper graph shows the profilometer scanning area, and the lower graph shows the scanning results. Figure 7 The profilometer analysis results of the perovskite thin film prepared in Comparative Example 2 are shown in the following graphs: the upper graph shows the profilometer scanning area, and the lower graph shows the scanning results. Figure 8 The profilometer analysis results of the perovskite thin film prepared in Comparative Example 3 are shown in the following graphs: the upper graph shows the profilometer scanning area, and the lower graph shows the scanning results. Figure 9 The profilometry analysis results for the perovskite thin film prepared in Example 4 are shown below: the top image shows the profilometry scanning area, and the bottom image shows the scanning results. (Comparison) Figures 5-9 It can be seen that the film prepared by the mass ratio of ethylene glycol and HI aqueous solution in the binary mixed solvent of 36:64 has a smoother edge and a more uniform thickness distribution, and its quality is significantly better than that of the film prepared by other ratios.
Claims
1. A method of screen printing a patterned perovskite thin film, characterized in that, The steps are as follows: S1. Substrate cleaning: Cut the substrate to the required size, clean it with a lint-free cloth and ethanol, place it on a PTFE cleaning rack, put it in an ultrasonic cleaner, add water and ethanol alternately in sequence, and ultrasonically clean it. After ultrasonic cleaning, remove the substrate and dry it with nitrogen. S2, hydrophilic treatment: Place the substrate cleaned by S1 into a plasma cleaner or a UV ozone cleaner for hydrophilic treatment. S3, Perovskite slurry preparation: After dry grinding of perovskite single crystals, a binary mixed solvent is added, and the mixture is wet ground until homogeneous to obtain a perovskite slurry. The raw material ratio is perovskite single crystal : binary mixed solvent = (3~5) g : (100~200) μL. The binary mixed solvent is prepared by mixing ethylene glycol and hydrohalic acid solution at a mass ratio of a : (100-a) and stirring until homogeneous. The value of a ranges from 24 to 48. The halogen in the hydrohalic acid is the same as that in the perovskite single crystal, and the concentration of the hydrohalic acid solution is 45~58 wt%. S4. Screen printing for preparing patterned perovskite wet films: A patterned stencil is horizontally fixed, and the substrate obtained in S2 is placed below the area to be printed on the stencil. The perovskite slurry obtained in S3 is evenly applied to the area to be printed on the stencil. The stencil is then pressed down with a squeegee until it contacts the substrate and passes through the area to be printed, thus obtaining a patterned perovskite wet film on the substrate. The pattern on the stencil corresponds to a preset pattern on the perovskite film: the preset pattern portion of the perovskite film is solid, and the corresponding pattern portion on the stencil is hollow; the preset pattern portion of the perovskite film is hollow, and the corresponding pattern portion on the stencil is solid; the stencil area corresponding to the area of the perovskite film without a preset pattern is solid. S5. Annealing treatment: The patterned perovskite wet film printed by S4 is annealed together with the substrate to obtain a patterned perovskite thin film.
2. The method of claim 1, wherein the screen printing is performed by using a screen having a mesh size of 100-400. In S1, the substrate is quartz, glass, silicon wafer or other flexible substrate. 3.The method of claim 1, wherein the screen printing is performed by using a screen having a mesh size of 100-400. In S2, the contact angle of the substrate after hydrophilic treatment is 0~50°. 4.The method of claim 1, wherein the screen printing is performed by using a screen having a mesh size of 100-400. In S3, the perovskite single crystal includes, but is not limited to, MAPbI3, PEA2PbI4, BA2MA3Pb4I 13 or Cs2AgBiBr6. 5.The method of claim 1, wherein the screen printing is performed by using a screen having a mesh size of 100-400. In S4, the mesh count of the stencil is 50~200 mesh. 6.The method of claim 1, wherein the screen printing is performed by using a screen having a mesh size of 100-400. In S5, the annealing conditions are 60~80℃ for 30~60min.